2021
DOI: 10.4254/wjh.v13.i2.242
|View full text |Cite
|
Sign up to set email alerts
|

Occult hepatitis C virus infection in the Middle East and Eastern Mediterranean countries: A systematic review and meta-analysis

Abstract: BACKGROUND The presence of hepatitis C virus (HCV) RNA in liver tissue or peripheral blood mononuclear cells with no identified virus genome in the serum has been reported worldwide among patients with either normal or elevated serum liver enzymes. The characterization of occult HCV infection (OCI) epidemiology in the Middle East and Eastern Mediterranean (M and E) countries, a region with the highest incidence and prevalence rates of HCV infection in the world, would be effective for more appropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…The existence of OCI in HD patients continues to be reported especially in regions showing a high prevalence of hepatitis C virus ( 19 ). Extensive studies on OCI have been conducted in European countries and the USA ( 7 , 11 , 13 , 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of OCI in HD patients continues to be reported especially in regions showing a high prevalence of hepatitis C virus ( 19 ). Extensive studies on OCI have been conducted in European countries and the USA ( 7 , 11 , 13 , 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies on OCI have been conducted in European countries and the USA ( 7 , 11 , 13 , 14 ). A systematic review related to OCI in the Middle East and Mediterranean countries revealed an overall prevalence of 10.04% ( 19 ). A prospective study at three dialysis centres in Chiang Mai, Thailand, suggested that OCI may be common among HD patients ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several Egyptian studies were conducted to detect the prevalence of occult HCV in different populations with numbers starting from 4% (19) to 20% (20) and 40.7% (21) . A metanalysis of different Middle Eastern studies showed that Egypt had an estimated prevalence ranging from 3.33-44.44% in different populations (22) .…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly OCI was also identified in an apparently healthy group from the general population-3.3% [87], and random blood donors from Spain, Mexico, and China-0.1-3.4% [88][89][90]. In Egypt, which has one of the highest HCV infection rates, the pooled OCI prevalence estimated by meta-analysis of studies on healthy populations reached 4.79% [83]. In fact, it is possible that OCI can be prevalent in other groups where the presence of HCV-specific T-cell responses without detectable viremia and seroconversion are frequently found, such as healthcare workers, prisoners, household contacts of CHC patients, and their spouses [91].…”
Section: Epidemiological Significance Of Ocimentioning
confidence: 95%
“…Persisting HCV was found in high-risk groups such as injection drug users-9.6-18.2% [77,78], patients with beta-thalassemia major-3.3-6.3% [38,79], hemodialysis patients-4.8-45% [80,81], or infectious liver disease-free subjects undergoing phlebotomy-1.27% [82]. A recent meta-analysis of studies on populations from the Middle East and Eastern Mediterranean countries estimated the pooled rate of OCI in patients diagnosed with cryptogenic liver disease to be 20.8% [83]. OCI was also shown to co-exist with HIV or HBV infections.…”
Section: Epidemiological Significance Of Ocimentioning
confidence: 99%